Association of follistatin and cytochrome p450 side-chain cleavage enzyme with polycystic ovarian syndrome - Nazir, Fouzia; Inayatullah, S.; Jalali, S. (International Journal of Health Sciences, 2022)
Objectives: Polycystic ovarian syndrome is a complex disorder commonly found in women in their reproductive age around the globe. Due to its higher clinical implications and communicability, this research article describes epidemiological studies and the association of known microsatellite markers with PCOS in the Pakistani population. Methods: Data were collected from 62 Pakistani women. The study involved pedigree analysis which revealed recessive mode of inheritance in all of them. The mendelian ratio in marriages between non-PCOS (male) and PCOS (female) individuals remained 1:1 while between non-PCOS (male) and non-PCOS (female) remained 3:1 respectively. Results: The result showed that there was an association of marker D15S519 (CYP11A, 10q24.3) with family 5 with an X2 value of 7.78 (p < 0.01) while a strong association of marker D5S822 (FS, 5p14) with an X2 value of 4.89 (p <0.05) was observed in family 2. In the case of family 1, a weak association of allele 1 with marker D19S212 (INSL3, 19p13.1) was observed with an X2 value of 2.25 (p > 0.10), While family 6 also presented a very weak association of homozygosity with marker D19S391 (INS receptor, 19p13.2) with X2 value of 3.45 (p ≥ 0.05). Conclusion: Findings indicated a higher prevalence of PCOS and highlights the emergence of more interventions to minimize the level of complications in women. Our intrusions intended to describe the genetic basis of PCOS in Pakistani population with special emphasis on large families in current study. Moreover, association of known loci for PCOS with our families.